Developing Repertoire: A Qualitative Study of Trainees’ Self-Reflection on Clinical Practice - De Stefano, Jack; Overington, Louise; Bradley, Stacy (Canadian Journal of Counselling and Psychotherapy, 2014)
Self-reflection is believed to be essential to competent practice and thus should be introduced early in clinical training. This study examined the self-reflective logs of 12 master’s level trainees to gain an understanding of the focus and content of their self-reflective thoughts and experiences while working with one client in counselling. Using consensual qualitative research methodology, 3 themes captured the bulk of their self-reflections: (a) the role of emotions in the learning process, (b) the client’s contributions to their learning, and (c) the intentional use of therapeutic building blocks. Implications for counsellors, supervisors, and training programs are discussed.